2018
DOI: 10.4103/ijciis.ijciis_40_17
|View full text |Cite
|
Sign up to set email alerts
|

Three- versus four-factor prothrombin complex concentrate for the reversal of warfarin-induced bleeding

Abstract: Objective:The objective of this study was to evaluate the effectiveness of 3-factor prothrombin complex concentrate (3F-PCC) compared to 4-factor PCC (4F-PCC) in warfarin-associated bleeding.Methods:This multicenter, retrospective, cohort study analyzed data from patients admitted between May 2011 and October 2014 who received PCC for warfarin-associated bleeding. The primary outcome was the rate of international normalized ratio (INR) normalization, defined as an INR ≤1.3, after administration of 3F-PCC compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…The proportion of patients who reached the goal INR was higher with PCC4 (87% vs. 31.6%, p < 0.001). Comparisons of PCC3 and PCC4 products for EWR have been done by others (17)(18)(19)(20)(21)(22)(23). Our study is similar to these other studies regarding retrospective design, PCC products compared, and the adult population.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The proportion of patients who reached the goal INR was higher with PCC4 (87% vs. 31.6%, p < 0.001). Comparisons of PCC3 and PCC4 products for EWR have been done by others (17)(18)(19)(20)(21)(22)(23). Our study is similar to these other studies regarding retrospective design, PCC products compared, and the adult population.…”
Section: Discussionsupporting
confidence: 81%
“…Given the compositional differences in the PCC products, it is important to know if there are differences in clinical response for effective and safe use of these products. Studies evaluating the comparative effects of PCC3 and PCC4 head-to-head for EWR with the outcome of INR lowering response and/or clinical outcomes are few (17)(18)(19)(20)(21)(22)(23). The inclusion criteria for these studies vary, but all were in adult patients needing reversal of warfarin for bleeding, surgical intervention, and/or trauma associated bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…However, given the critical need to reverse the effects of warfarin in the setting of an emergent bleeding episode, a randomized trial would be difficult to implement. Several previous studies compare the effectiveness of PCC3 and PCC4 for EWR with the outcome of INR lowering response and/or clinical outcomes [23][24][25][26][27][28][29]. The inclusion criteria for these studies vary, but all were in adult patients needing reversal of warfarin for bleeding, surgical intervention, and/or trauma associated bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Holt, et al studied multiple centers with warfarin reversal defined as an INR ≤ 1.3. Regardless, a greater proportion of PCC4 patients achieved goal INR compared to PCC3 patients (PCC4: 48/57 (84.2%) vs. PCC3:40/77 (51.9%), p < 0.001) (patient counts calculated from percentages and total patient number) [ 27 ]. DeAngelo, et al reported analysis from two centers with institutions with the same formulary and protocols.…”
Section: Discussionmentioning
confidence: 99%
“…There is recent evidence that 4F-PCCs effectively reduce INR in patients with VKA-associated bleeding, with TEE rates ranging from 1.8 to 6.5% [48,49] data from a meta-analysis of PCC use in VKAassociated ICH support these findings [50]. 4F-PCC was shown to reduce INR more effectively compared with 3F-PCC alone [48], but not compared with 3F-PCC + rFVIIa [49]; however, 4F-PCC has also been associated with a significantly lower rate of TEEs compared with 3F-PCC + rFVIIa [49]. In contrast, one recent retrospective study of emergency department data reported an increased rate of TEEs in patients on warfarin who received 4F-PCC compared with FFP [51].…”
Section: Recent Evidence For Anticoagulant Reversalmentioning
confidence: 99%